Evaluation of data-driven sustainability potential at SMEs using an altered ecocanvas model - Levente Péter Bálint; László Várallyai; Szilvia Botos (Economies, 2025)
Incorporating sustainability into business operations is likely to become one of the most significant priorities and challenges for companies in the near future. SMEs operating within conventional frameworks often experience constraints when adjusting to evolving circumstances. They frequently lack resources, qualified experts, skills, and capabilities to enable the efficient implementation of DT within the organization. In this paper, Eurostat datasets were analyzed to uncover trends in SME digitalization and sustainability, focusing on patterns in data utilization, employee training, and environmental considerations. These insights were integrated into an altered Ecocanvas sustainability modeling tool to develop a framework supporting their strategic planning and decision-making. It has proven to be a useful tool for this purpose by mapping business processes against sustainability and strategic goals while indicating where digital or alternative solutions can be introduced. SMEs analyze data and consider environmental impacts at different levels based on their size categories. To determine whether these differences are statistically significant, we have performed one-way ANOVA tests. This paper aims to provide a data-driven situational analysis and tool, which outlines the benefits of data analytics from several aspects while offering practical recommendations for company leaders to consider and implement.
Keywords: 330; sustainability; Ecocanvas; ESG; reporting; barriers; SMEs; data-driven